(3GdLGeY aj GdbQGAGJ GdYTQ hbQGAI GdCYeTs - (3eMeO Hf LQjQ Hf jRjO GdWHQj , GHf LQjQ, CHh LYaQ, J (B310 (3g` s
(3ChdgG (B:s
(3SCdfj habc Gddg GdgOi hLfHc GdQOi Cf CLeY dc ai GdLGeY PcQ bQGAGJ GdbQGA GdYTQI s
(3BNQgG (B:s
(3Pdc cdeI aUGQ YOO cdeGJ ef aYd Pdc Cbd ef YOO cdeGJ ef de jaYd Pdc aEdi gPG ENJdGa aj YOO GdMQha EfJgJ gPg GdCbSGe GdePchQI hGdMeO ddg hMOg Je s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B147s
Keywords: (3GdbQGAGJ hGdJLhjOs